Some Elements of the Regime of Management of Irrelevance in Science. Issue 1 (2nd January 2022) - Neves, Fabrício Monteiro
Abstract: In contexts of scientific production deemed peripheral, knowledge produced is depicted in a condition of inferiority relative to that produced in other contexts; the daily practice of science is then guided by values and procedures, be they conscious or not, of peripheralization. This research note discusses the constitution, reproduction and generalization of peripheralization into what I call a regime of management of irrelevance in science: a scientific process with its own pragmatic and value content, whose elements will be presented in this work. These elements were identified during field research in laboratories and interviews with key interlocutors (research leaders) of biotechnology research teams in Brazil. What matters here is instead of taking the center/periphery dichotomy as an objective structure of the scientific system—a common approach in science and technology studies—it is shown as expecta-tions with practical repercussions.